2012
DOI: 10.1093/mutage/ges031
|View full text |Cite
|
Sign up to set email alerts
|

In vivo validation of DNA adduct formation by estragole in rats predicted by physiologically based biodynamic modelling

Abstract: Estragole is a naturally occurring food-borne genotoxic compound found in a variety of food sources, including spices and herbs. This results in human exposure to estragole via the regular diet. The objective of this study was to quantify the dose-dependent estragole-DNA adduct formation in rat liver and the urinary excretion of 1'-hydroxyestragole glucuronide in order to validate our recently developed physiologically based biodynamic (PBBD) model. Groups of male outbred Sprague Dawley rats (n = 10, per group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 29 publications
0
37
0
Order By: Relevance
“…In a previous study by Paini et al . () such a PBD model for liver DNA adduct formation was developed and validated in an in vivo study for estragole DNA adduct formation in the liver of rats. This study also revealed that not only bioactivatoin to the reactive 1′‐sulfooxymetabolite but also DNA adduct formation in rat liver was linear with the dose of estragole (Paini et al ., , ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study by Paini et al . () such a PBD model for liver DNA adduct formation was developed and validated in an in vivo study for estragole DNA adduct formation in the liver of rats. This study also revealed that not only bioactivatoin to the reactive 1′‐sulfooxymetabolite but also DNA adduct formation in rat liver was linear with the dose of estragole (Paini et al ., , ).…”
Section: Discussionmentioning
confidence: 99%
“…This study also revealed that not only bioactivatoin to the reactive 1′‐sulfooxymetabolite but also DNA adduct formation in rat liver was linear with the dose of estragole (Paini et al ., , ). Development of such PBD models for liver DNA adduct formation in human could be achieved by combining the existing human PBK models with data on alkenylbenzene concentration‐dependent DNA adduct formation in isolated human hepatocytes as done for rat hepatocytes exposed to estragole previously (Paini et al ., , Paini et al ., ). Such studies in primary hepatocytes are likely to also account for possible repair and stability of the alkenylbenzene adducts and would thus provide insight in whether formation of adducts, even during a short period, could have irreversible effects and thus be deleterious, or whether they are likely to be repaired, thereby decreasing risk.…”
Section: Discussionmentioning
confidence: 99%
“…The first group, representing the control group, was dosed once with 150 mg/kg bw estragole only. In a study by Paini et al , the dose of 150 mg/kg bw was the lowest dose of estragole able to induce significant levels of estragole DNA adducts (E‐3′‐ N 2 ‐dGuo) in the liver of male outbred Sprague‐Dawley rats 48 h after gavage compared to the solvent control (vehicle) group. The second group was dosed once with 150 mg/kg bw estragole and 87.2 mg/kg bw of nevadensin.…”
Section: Methodsmentioning
confidence: 99%
“…These models can be used to extrapolate from benchmark dose causing 10 % extra tumour incidence (BMD 10 ) down to the so-called virtual safe dose (VSD) (the dose resulting in one in a million extra tumour incidence upon life time exposure). Additionally, a PB-TD model was developed, by measuring formation of estragole DNA adducts in rat primary hepatocytes and was further validated in vivo with male SD rats (Paini et al, 2012). Additionally, a PB-TD model was developed, by measuring formation of estragole DNA adducts in rat primary hepatocytes and was further validated in vivo with male SD rats (Paini et al, 2012).…”
Section: Application In Hazard Assessmentmentioning
confidence: 99%